2013
DOI: 10.1007/s00431-013-2018-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term body composition and metabolic changes in HIV-infected children switched from stavudine to tenofovir and from protease inhibitors to efavirenz

Abstract: patients, after switching from d4T to TDF and from PI to EFV, show most of the changes in anthropometry and body composition associated with normal growth and no frankly pathological change in metabolic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
0
16
0
2
Order By: Relevance
“…This same cohort was reevaluated again 8 years after the treatment switch and showed no frankly pathologic abnormalities of body composition. 83 Recommended treatment strategies include lifestyle changes such as a calorically appropriate low-fat diet; exercise (especially strength training); and smoking cessation, if applicable, to decrease future cardiovascular risk. Proposed treatments include metformin and thiazolidinediones, but data regarding their efficacy are lacking in children.…”
Section: Managementmentioning
confidence: 99%
“…This same cohort was reevaluated again 8 years after the treatment switch and showed no frankly pathologic abnormalities of body composition. 83 Recommended treatment strategies include lifestyle changes such as a calorically appropriate low-fat diet; exercise (especially strength training); and smoking cessation, if applicable, to decrease future cardiovascular risk. Proposed treatments include metformin and thiazolidinediones, but data regarding their efficacy are lacking in children.…”
Section: Managementmentioning
confidence: 99%
“…Among the factors that may be implicated in atherosclerotic disease, dyslipidemia and inflammation are the most important [ 1 5 ]. The abnormalities in carbohydrate metabolism are evident [ 2 5 ], but less common complications [ 6 ], although other studies have not demonstrated any impairment [ 7 , 8 ]. The occurrence of these cardiovascular risk factors in childhood and adolescence has been associated with intima-media thickening of the carotid artery (IMTc) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reversibility of fat loss after ceasing of stavudine treatment is still debated [ 25 , 26 ]. In our cohort a subgroup of 26 children switched from stavudine to another NRTI (predominantly abacavir) and had DEXA assessments before as well as after this switch.…”
Section: Resultsmentioning
confidence: 99%